Pattern of European Regional Creativity: Exploring Endogenous Sustainability - Lishchynskyy Ihor; Lyzun Mariia (ECONOMICS)
During the latest decades, regional creativity has often been considered as the precondition for innovativeness and sustainability. However, quantitative indicators of creativity are the subject of discussion. The paper aims to analyse the patterns and causes of European regional creativity distribution, revealing the influence of endogenous determinants on regional innovative development. An empirical analysis of regional patenting activity and a selection of indicators of regional creativity is conducted. Among the indicators, we include the development of regional institutions that are assessed through the data of the European Quality of Government Index. Besides the learning ability of the region (indicators of higher education prevalence and digital skills), the abundance of the creative class, regional innovative infrastructure, and population agglomeration were taken into account. The paper concludes concerning the most crucial factors contributing to endogenous sustainability through the lenses of European regions. In general, the formed model turned out to be significant with an acceptable level of standard error and a high predictive value. The influence of most of the parameters (except for the intelligence) was positive and significant. It is especially worth highlighting the parameters of regional institutions’ quality and volumes of private research and development expenditures, which exert the greatest positive influence on the resulting variable.